Historical land use changes of Jempol, Negeri Sembilan in the twentieth century - Abd. Manan, Mohd Shahrudin; Hashim, Nor Rasidah (Faculty of Environmental Studies, Universiti Putra Malaysia, 2009)

(untitled)
Land use is anthropogenic activities as a way for humans to manipulate, modify andadapt with their environment (Singh et al., 2001; Milanova et al., 2005). The activitiesgive significant impacts on the Earth’s surface thus become reliable interface inunderstanding spatial interaction between human and environment (Mandal, 1982;Lawson, 2001; Legg, 2007). Analyzing past land uses is useful to understand patterns of land use changing over time besides also worthy for heritage conservation projects sinceit requires and dependant on the availability of complex historical information rangingfrom the geo-morphological characteristics to demographic patterns of the area interest.